(untitled) (MMIT Proceedings, 2025)
In this era of rapid development, both young people receiving education and educators must keep pace with this era. There are also ideas for the development of the education sector. In this article, the author also highlights the history of "pedagogy" and "artificial intelligence" and how it is reflected in the educational process. It analyzes which artificial intelligence applications and for what purpose teachers can use in our lessons, writes what results they will achieve